Pengaruh Leverage dan Kepemilikan Institusional terhadap Tax Avoidance dengan Profitabilitas sebagai Variabel Moderasi - Muhammad Ilham Maulana; Suwandi Suwandi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the effect of leverage and institutional ownership on tax avoidance, with profitability as a moderating variable, in plantation sector and mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This study employs a quantitative research method. The sample was selected using a purposive sampling technique, resulting in 16 companies as the research sample, with a total of 80 observations. Data analysis is conducted using multiple linear regression and moderated regression analysis (MRA). The results indicate that leverage and institutional ownership do not have a significant effect on tax avoidance. Furthermore, profitability is unable to moderate the relationship between leverage and tax avoidance as well as between institutional ownership and tax avoidance. This study has limitations related to the relatively small sample size, as many companies experienced losses during the observation period and therefore did not meet the sample selection criteria.